Analysis of Signalized Intersection Performance Improvement on PHH. Mustofa Road Section, Bandung City Based on Coordination Intersection Modeling - Akbardin, Juang; Hendrawan, Priandhany; Ma’soem, Dadang Mohamad (Universitas Ibn Khaldun Bogor, 2025)
The rapid population growth in the city of Bandung has an impact on increasingly complex problems, especially the increase in traffic flow that is not balanced with the availability of road capacity. This will certainly cause congestion, one of which is at the intersection point. On Jalan PHH. Mustofa several signalized intersections are close to each other which often cause congestion. Data was collected through direct surveys in the field and obtained from third parties. The calculation of signalized intersection performance was carried out using Microsoft Excel, PTV Visum and PTV Vissim software. The vehicle growth rate that occurred in the city of Bandung in 2040 was 3.133%. And the number of vehicles in the city of Bandung in 2040 was 3,339,659 vehicles. The most effective cycle time in improving intersection performance on Jalan PHH. Mustofa with coordination modeling is 51 seconds. Based on the results of the development of signalized intersections on the PTV Vissim application, the results obtained decreased queue length and delay so that the level of service at the North Cikutra Intersection received a class A service level, the South received a class B service level and the West received a class C service level. For the Cimuncang Intersection, the North arm service level received a class A service level, the South received a class C service level and the West received a class C service level. And for the Padasuka Intersection, the North arm service level received a class B service level and the West received a class C service level.